ANALISA DEBIT BANJIR MENGGUNAKAN METODE NAKAYASU DAN SCS (SOIL CONSEVATION SERVICES) SEBAGAI PENENTUAN TINGGI MUKA AIR DI SUNGAI SEMBAKUNG, KECAMATAN LUMBIS PANSIANGAN KABUPATEN NUNUKAN - Sulistyani, Kiki Frida; Suhudi, Suhudi (BUANA SAINS, 2024)
This research aimed to estimate the magnitude of the flood discharge value in the Sembakung River using the Nakayasu Method and SCS (Soil Conservation Services) as a determination of water level. This study was located in the upstream Sembakung Watershed and divided into two sub-watersheds such as Labang 1 and Labang 2. The Calculation of flood discharge using the Nakayasu and SCS method was calibrated with the results of hydrometric measurements. Based on the results of hydrometric measurements, floods that often occur in the Labang Sub-watershed are at an altitude of +117 - +118 with a large discharge ranging from 633 - 828 m3 / sec. The maximum flood in the Labang sub-watershed was at an altitude of +120, with a discharge of 1,271 m3 / sec. The calculation result of the SCS method is 1,280 m3 / sec and the Nakayasu method is 3,310 m3 / sec. The closest measurement result is the SCS method. River profile calculation using HEC-RAS software, with flood discharge at Labang 1 location and downstream boundary in the form of flood discharge at Labang 2 location. The results of HEC-RAS modeling using flood discharge with a return period of 25 years in the Labang 1 Sub-DAS obtained a water level elevation of +120.89. While the results of modeling with flood discharge with a return period of 50 years are at an altitude of +122.71.